2019
DOI: 10.1158/1541-7786.mcr-18-1235
|View full text |Cite
|
Sign up to set email alerts
|

TFE3 Xp11.2 Translocation Renal Cell Carcinoma Mouse Model Reveals Novel Therapeutic Targets and Identifies GPNMB as a Diagnostic Marker for Human Disease

Abstract: Renal cell carcinoma (RCC) associated with Xp11.2 translocation (TFE3-RCC) has been recently defined as a distinct subset of RCC classified by characteristic morphology and clinical presentation. The Xp11 translocations involve the TFE3 transcription factor and produce chimeric TFE3 proteins retaining the basic helix-loop-helix leucine zipper structure for dimerization and DNA binding suggesting that chimeric TFE3 proteins function as oncogenic transcription factors. Diagnostic biomarkers and effective forms o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 56 publications
7
50
0
Order By: Relevance
“…4A and Supplementary Data 5 ). Among them, GPNMB , HIF1A , MET , and BIRC7 , which were previously reported to have higher expression in tRCC 16 , 17 , were also upregulated in our TFE3 -tRCC cohort (Supplementary Figure 8A). Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis identified that lysosomal, autophagy, and innate immunity pathways were significantly upregulated in TFE3 -tRCC (Fig.…”
Section: Resultssupporting
confidence: 59%
“…4A and Supplementary Data 5 ). Among them, GPNMB , HIF1A , MET , and BIRC7 , which were previously reported to have higher expression in tRCC 16 , 17 , were also upregulated in our TFE3 -tRCC cohort (Supplementary Figure 8A). Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis identified that lysosomal, autophagy, and innate immunity pathways were significantly upregulated in TFE3 -tRCC (Fig.…”
Section: Resultssupporting
confidence: 59%
“…To investigate roles of ANGPTL2 in development and progression of tRCC, we generated Chd16-Cre/ Rosa LSL-PRCC-TFE3/+ mice that specifically induce the PRCC-TFE3 fusion gene in renal tubular epithelial cells (Supplemental Fig. S1A; Baba et al 2019;Kurahashi et al 2019). Chd16-Cre/Rosa LSL-PRCC-TFE3/+ mice developed renal cell carcinoma characterized by dilated renal tubules and cyst formation by 40 wk of age, with an incidence of 100%, and their median survival time was 344 d. To evaluate ANGPTL2 function in renal cancer progression, we crossed Chd16-Cre/Rosa LSL-PRCC-TFE3/+ mice with ANGPTL2 mutant mice (either Angptl2 −/− or Angptl2 F/F mice) to achieve ANGPTL2 deficiency in either the whole body or specifically in renal tubular epithelial cells, respectively ( Fig.…”
Section: Angptl2 Expression In Tumor Versus Stromal Cells Has Opposinmentioning
confidence: 99%
“…Prior case series have suggested that tRCC has a demographic profile that is distinct from more common subtypes of kidney cancer, with a younger age at diagnosis, advanced stage at presentation, and a female predominance [3][4][5] . Biologically, tRCCs are driven by activating gene fusions involving transcription factors in the MiT/TFE gene family [6][7][8][9][10][11][12] . There are currently no molecularly-targeted therapies specific to tRCC and effective treatments for this aggressive cancer remain a major unmet medical need.…”
Section: Introductionmentioning
confidence: 99%